A Sustainable Polymer Composite from Recycled Polypropylene Filled with Shrimp Shell Waste - Mohamad, Noraiham; Abd Latiff, Anisah; Ab Maulod, Hairul Effendy; Asyadi Azam, Mohd; Mohd Edeerozey, Abd Manaf (Taylor & Francies, 2014)
This research explores the potential of using recycled polypropylene (PP) incorporated with shrimp shell waste to produce a sustainable polymer composite. In this study, the mechanical and physical properties of recycled polypropylene/shrimp shell (rPP/SS) composites prepared by melt compounding and compression molding techniques were evaluated. The effects of SS loading were investigated by using various compositions of rPP/SS composites, ranging from 0 to 8 wt% SS that consists of two different sizes, i.e., fine and coarse SS. The composites were tested for their mechanical and physical properties using impact, tensile and water absorption tests. Furthermore, the morphology of the composites was examined by using a Scanning Electron Microscopy (SEM). Incorporation of SS was found to increase the Young’s modulus of the rPP, but the impact and tensile strength showed a decrease. However, we observed that both the impact and tensile strength improve with the further increase of the SS content. In other words, composites with high shrimp shell loading were observed to exhibit better tensile and impact properties compared to composites with low shrimp shell loading. Moreover, at 8 wt% of SS, the value of tensile strength is comparable to that of neat rPP